Birds of associated sites to tropical forest in the Chiapas´s Central Depression, Mexico. - Ramírez-Albores, Jorge E. (Instituto de Ecología, A.C., 2010)
This paper describes the birds’ structure and composition of associated sites to tropical forest in the Central Depression of Chiapas, Mexico, through 2003 to 2004. I recorded 364 species considering scientific literature, museum collections and field work. Families with highest species richness were Tyrannidae, Parulidae, Icteridae and Trochilidae. Resident birds represented 68% of the total and the 32% remaining were migratory. Thirty four percent of bird species were rare, 11% common and 3% abundant. Highest species richness was found for the tropical deciduous forest (226), followed by the secondary forest (163) and the tropical semideciduous forest (122). From all birds, 136 were additional records in the region and, 56 were for the Sumidero Canyon National Park. The species richness recorded included 45% of the avifauna of Chiapas, indicating the relevance of this region and the urgent need to establish conservation and protection management strategies. The magnitude of species increment and lack of information in this region suggest that regional and local inventories are necessaries to improve the knowledge about species distribution.